2020
DOI: 10.17944/mkutfd.790954
|View full text |Cite
|
Sign up to set email alerts
|

Gaitada Gizli Kan Pozitifliği Nedeniyle Kolonoskopi Yapılanlarda Kolorektal Malignite Sıklığı

Abstract: Kolorektal kanserlerin erken evrede belirlenmesi, prognozun iyileştirilmesindeki en önemli kısımdır. Bunun yolu etkili tarama programlarından geçmektedir. Gaitada gizli kan testi tarama yöntemlerinin başında gelmektedir. Bu çalışmada endoskopi ünitemizde gaitada gizli kan testi pozitifliği nedeniyle kolonoskopi yapılan hastalarda kolonoskopik bulguları değerlendirmeyi, polip sıklığını, histopatolojik tiplerini ve kolorektal malignite sıklığını saptamayı amaçladık. Materyal ve Metod: 2018 Aralık ve 2019 Temmuz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
0
2
Order By: Relevance
“…Quyn et al 20 . reported a 7.1% CRC detection rate in their series of 53,332 cases of FOBT positivity in the screening group, and our findings were similar to several similar studies 12,18 . There are also studies with a lower rate of CRC compared to our study 15,16,19 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Quyn et al 20 . reported a 7.1% CRC detection rate in their series of 53,332 cases of FOBT positivity in the screening group, and our findings were similar to several similar studies 12,18 . There are also studies with a lower rate of CRC compared to our study 15,16,19 .…”
Section: Discussionsupporting
confidence: 93%
“…In the study conducted by Levi et al 11 on 16,359 people, of the 2.266 participants undergoing FOBT, 88 (3.9%) tests were positive. In many similar studies, FOBT positivity rates were found to be lower than in our study [12][13][14] . We can attribute the higher rate of FOBT positives in our results, compared to other studies, to the fact that our target group screened with PHE consisted of people aged 50 and over.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation